Ecological niche partitioning and resource utilization in two sympatric lacertid lizard species (Meroles anchietae and M. cuneirostris) from the Namib Desert - Chimimba, Christian Timothy (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2018.